Saudi children's thoughts on inclusive education. Issue 5 (4th May 2017) - Dare, Lynn; Nowicki, Elizabeth; Felimban, Huda
ABSTRACT: Saudi Arabia has followed the global trend towards inclusive education; however, few researchers have examined the lived reality of inclusion in Saudi schools. In this study, we interviewed 31 girls and 34 boys in grades 5 and 6 who attended an inclusive school in Saudi. The overarching research question was, 'How do Saudi children perceive social exclusion or inclusion among their classmates with learning difficulties?' We followed a phenomenological approach, reporting descriptions in the participants' own words. We identified two overarching groupings of responses that related to beliefs and behaviours. Students in our study voiced a variety of beliefs about why children with learning difficulties might be socially accepted or not accepted. More boys than girls believed that students with learning difficulties were socially accepted. Students gave examples of inclusionary behaviour they had witnessed or been involved in, and these examples emerged more strongly than examples of exclusionary behaviour. Inclusionary behaviours included friendship, helping with schoolwork, and including in play.